(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
In the recent past, a major interest in the control of blood sugar had been targeted to develop plenty of new formulations.The present work aims at the development of a low cost sustained release system of metformin hydrochloride embedded in microspheres of agar (Gelidium cartilagineum) to overcome the frequent dosing of the drug. Models were developed with respect to controlling variables (X1, drug: Polymer, X2, surfactant concentration, and X3, pH of phosphate buffer).The most effective levels of parameters were found as X1 (1:2), X2 (1.25%), X3 (phosphate buffer pH 7.4). Instrumental analysis (Fourier transforms infraâ€red spectroscopy, differential scanning calorimetry, Xâ€ray diffraction and scanning electron microscopy),mucoadhesion study, toxicity test and in vivo study were performed with the optimized product.The best batch (A2) exhibited a high drug entrapment efficiency of 84.82 Â± 1.23%, swelling index of 3.84 Â± 0.38% and 86% of mucoadhesion after 12h. The in vitro release was also sustained for more than 12 h.